DEVELOPMENT AND EVALUATION OF ASYMMETRIC MEMBRANE CAPSULE OF KETOROLAC TROMETHAMINE - Kaur, Rupinder; Singh, Sukhdev; Hassan, Aaliya; Jalhan, Sunny (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
ABSTRACT Objective: Osmotic systems for moderate to low water soluble drugs are limited because of the more thick coatings impede the permeability. To overcome this problem, asymmetric membrane osmotic drug delivery systems have been developed. Method: In present investigation asymmetric membrane capsules (AMC), having in-situ pores for achieving the osmotic controlled release of ketorolac tromethamine, were successfully designed by using cellulose acetate (CA 398-10) as semi-permeable membrane forming polymer and glycerol, PEG-400 as pore forming agent andÂ osmotic agents viz. sodium chloride, fructose and mannitol. Result: The prepared AM capsules were physically evaluated for various parameters such as length, weight variation, thickness, elongation at break, tensile strength, void volume determination and surface characterization. Results of SEM studies inveterate the formation of pores in the asymmetric membranes after coming into contact with the aqueous environment. in- vitro release profile of ketorolac tromethamine were investigated. It is evident from results that the percent of drug released with glycerol was fund to be highest, followed by PEG-400. No significant change was observed in stability study of AMC. Conclusion: It was concluded that the drug release rate increase with the amount of osmogent due to increase in water uptake hence increased driving force for drug release. The percent drug released at the end of dissolution time from the control capsule (containing drug only) was lower as compared to capsules filled with various proportion of drug/osmogents. Â Keywords: of ketorolac tromethamine, asymmetric membrane capsules, cellulose acetate, osmotically controlled gastroretentive delivery